Automatic detection of automobiles for statistical purposes - Crisostomo, Jonathan
This is a software that processes snapshots of roads to recognize the vehicles and their corresponding types. Its main purpose is to develop a system that will reliably report road statistics based on visual input. The vehicle types to be classified are cars, trucks, jeeps and buses. A major tool that will be used in this project is MVTec Halcon 6.0 which is a computer vision software. The possible uses of the developed software are minimizing human effort in gathering data regarding the volume of cars passing through a road. The data in turn, can be used is assisting the improvement of traffic management on roads, helping in projecting maintenance schedules for heavily used roads, and maximizing resources on road control and management.